Modeling of the Stress–Strain of the Suspensions of the Stators of High-Power Turbogenerators - Oleksii Tretiak; Dmitriy Kritskiy; Igor Kobzar; Victoria Sokolova; Mariia Arefieva; Iryna Tretiak; Hromenko Denys; Viacheslav Nazarenko (Computation, 2022)
In the submitted scientific work, the existing types of stator fastening design of turbogenerators and the main causes of the stressed state of the stator suspensions are considered. A detailed calculation of the complex stressed state of the turbogenerator stator suspension was carried out for a number of electrical sheet steels, taking into consideration the unevenness of the heat distribution along the horizontal axis of the unit. It is proposed that the calculation of the mechanical stress is carried out by means of the mechanical and thermal calculation, coordinated with the electrical one. The possibility of replacing steel 38Х2Н2ВА with steel 34CrNiMo6 and 40NiCrMo7 is indicated, subject to compliance with GOST 8479-70 for the same strength group.